Grover Cleveland Loening papers - Loening, Grover, 1888-1976.
Correspondence; manuscripts of books, articles, and speeches; and subject files, newspaper clippings, scrapbooks, photographs, drawings, blueprints, and printed material documenting Loening's career in aviation. Includes material on his studies at Columbia University, employment at the Wright Aeronautical Corporation (chief engineer, 1913-1914), service in the U.S. Army Signal Corps Aviation Section, work at the Sturtevant Aeroplane Company, and establishment of the Grover Loening Aircraft Company. Other papers relate to his activities as an aviation consultant to the federal government and to private industry, particularly his service on the War Production Board, National Advisory Committee for Aeronautics, President's Air Policy Commission, and National Air Museum advisory board and his involvement with All American Aviation, Curtiss-Wright Corporation, Fairchild Engine and Airplane Corporation, Grumman Aircraft Engineering Corporation, New York Airways, Pan American Airways Corporation, and Platt-LePage Aircraft Corporation. Other topics include the flights of Charles A. Lindbergh, Richard Evelyn Byrd's first Antarctic expedition, and helicopter design and production.
Correspondents include Winthrop W. Aldrich, Vincent Astor, Richard Evelyn Byrd, Ira Eaker, Harry Hopkins, Joseph P. Kennedy, Andrew W. Mellon, William Mitchell, Eddie Rickenbacker, Winthrop Rockefeller, Igor Ivan Sikorsky, Harold S. Vanderbilt, and Orville and Wilbur Wright.
Smithsonian Institution National Air and Space Museum.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Aviation consultant, engineer, author, and aircraft manufacturer. Died 1976.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aldrich, Winthrop W. -- 1885-1974 -- Correspondence; Astor, Vincent, -- 1891-1959 -- Correspondence; Byrd, Richard Evelyn, -- 1888-1957 -- Correspondence; Eaker, Ira, -- 1896-1987 -- Correspondence; Hopkins, Harry L. -- 1890-1946 -- Correspondence; Kennedy, Joseph P. -- 1888-1969 -- Correspondence; Lindbergh, Charles A. -- 1902-1974.; Mellon, Andrew W. -- 1855-1937 -- Correspondence; Mitchell, William, -- 1879-1936 -- Correspondence; Rickenbacker, Eddie, -- 1890-1973 -- Correspondence; Rockefeller, Winthrop, -- 1912-1973 -- Correspondence; Sikorsky, Igor Ivan, -- 1889-1972 -- Correspondence; Vanderbilt, Harold S. -- 1884-1970 -- Correspondence; Wright, Wilbur, -- 1867-1912 -- Correspondence; Wright, Orville, -- 1871-1948 -- Correspondence; All American Aviation (Firm); Columbia University -- Students; Curtiss-Wright Corporation; Fairchild Engine and Airplane Corporation; Grover Loening Aircraft Company; Grumman Aircraft Engineering Corporation; National Air Museum (U.S.); New York Airways, Inc; Pan American Airways Corporation; Platt-LePage Aircraft Corporation; Sturtevant Aeroplane Company; United States. -- Army. -- Signal Corps. -- Aviation Section; United States. -- National Advisory Committee for Aeronautics; United States. -- President's Air Policy Commission; United States. -- War Production Board; Wright Aeronautical Corporation; Aeronautics; Aircraft industry -- United States; Flight; Helicopters; Antarctica -- Discovery and exploration; Aircraft manufacturers; Authors; Aviation consultants; Engineers